Geochronology and petrogenesis of late-Variscan plutonism (NW Portugal) : synthesis and inferences on crustal recycling and growth - Dias, G. (2009)
In NW Portugal large volumes of granitoids were emplaced during the post-collisional stage of the Variscan orogeny. This was the main period of successive granite generation, which exhibit different chemical and isotopic signatures. Geochronological and petrogenetic results are presented and inferences on the geodynamic evolution of the Iberian Variscides are discussed.